Fish waste Utilization with Reference to Fish Protein Hydrolysate – A Review - Wangkheirakpam, M. R.; Mahanand, S. S.; Majumdar, R. K.; Sharma, S.; Hidangmayum, D. D.; Netam, S. (Fishery Technology, 2019)
Aquaculture and capture fisheries have contributedto the global economy for decades, supportinglivelihood as well as nutritionall status. The sectorhas been growing substantially that more than 60%by-products as waste are generated which includesskin, head, frames, fins and viscera. With anincreasing population with limited resource andfood supply, the need for utilizing the discardedwaste have added interest in many processingindustries. This review discusses on hydrolysis ofun-utilised fish and fish waste which are rich sourceof nutrient that can impart stability in foodproducts, possess noble pharmaceuticals andneutraceuticals significance to health. Fish proteinhydrolysate has attracted much attention as anexcellent source of bioactive peptides impartingantioxidant, antihypertensive, immunomodulatoryand antimicrobial properties with a good balance ofessential amino acids. Above all, the review alsoreveals the present status and future potential ofutilizing fish waste into economically and sustainableproducts for human consumption.